Produksi Crude Selulase dari Bahan Baku Ampas Tebu Menggunakan Kapang Phanerochaete chrysosporium - Sri Rulianah; Zakijah Irfin; Mufid; Prayitno (Jurnal Teknik Kimia dan Lingkungan, 2017)
Bagasse contain high cellulose which potentially to be used to raw material for producing cellulase enzyme using fungi Phanerochaete chrysosporium. This fungus has ability to produce cellulase enzymes from substrates which contain cellulose and also produce enzymes that can degrade lignin content so it didn’t need the delignification process. The objective of this study was to convert cellulose in bagasse to be crude cellulase enzymes by using Phanerochaete chrysosporium and determine the effect of substrate concentration and fermentation time to the enzyme activity. This research was conducted by drying and reducing the bagasse particle size, rejuvenating mold Phanerocheate chrysoporium, making inoculum in liquid medium, fermenting bagasse in accordance with the variable, with media NLM (nitrogen limited media) using Phanerocheate chrysoporium. Fermentation results were filtered, and it was analyzed the activity of crude cellulase. The variable in this study was the time of fermentation 9, 11, 13, 15, and 17 days and substrate concentration: 5, 6, and 7 % b/v. Crude cellulose was filtered and was analyzed the enzyme activity by DNS (dinitro salicylic acid) reagent, using UV-Vis spectrophotometer. The best result of this study was the crude cellulase with highest activity 91,304 U/mL for 7 % substrate concentration with fermentation time 17 days.